Effect of Audit Quality, Geographic Diversification, Industry Diversification, Ownership Structure, and Audit Engagement Period on Earnings Management - Tia Maudi Prastitasari; Effriyanti Effriyanti (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2022)
This research is quantitative research with the descriptive method, the data used are secondary data in the form of financial reports that contain numbers and then tested and describe or provide an overview of these results. This study aims to see the effect of audit, geographic diversification, industry diversification, ownership structure, and audit engagement period on earnings management in manufacturing companies listed on the IDX for the 2017-2019 period. The population in this study were 118 companies. The sampling technique used purposive sampling and obtained 18 companies with a research period of 3 years (2017-2019) in order to obtain 54 sample data. The results showed that audit quality had a negative and significant effect on management earnings, geographic diversification had no effect on management earnings, industry diversification had no effect on earnings management, ownership structure, both institutional ownership and managerial ownership had no effect on earnings management, and audit tenure had a positive effect. and significant to earnings management. Simultaneously audit quality, geographic diversification, industry diversification, ownership structure and audit engagement period have a joint influence on earnings management in manufacturing companies listed on the IDX in 2017-2019.